Diaphragm, battery roll core, battery and preparation method
The core stress problem is solved by using hydrogen bonding between soft template particles on the base film that can be dissolved in the electrolyte solution and fluoropolymer in the lithium-ion battery core, which extends the cycle life of the battery and improves performance.
Patent Information
- Application Number
- CN202411315502.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2024-12-20
AI Technical Summary
The existing technology has shortcomings in solving the problem of stress in lithium-ion battery core, and the variable tension adjustment technology cannot effectively slow down the release of stress during the cycle. The positive electrode sheet embossing process can easily lead to poor powder loss and hot pressing and flattening effects. , reduce battery performance and life.
Using a separator, including a base film and soft template particles that can be dissolved in the electrolyte solution distributed on the surface of the base film, the spatial distance between the positive electrode and the negative electrode is increased by the soft template particles, forming an effective gap, combining fluorine-rich polymer and The hydrogen bond adsorption connection of functional functional groups ensures stable distribution of soft template particles on the surface of the base film, avoiding powder loss and poor flatness of hot pressing.
Effectively slow release of stress during the rolling core cycle, extend the cycle life of the battery, improve the reliability and safety of the battery, avoid the defect of positive electrode sheet embossing, and improve the overall performance of the battery.
Smart Images

Figure CN119171007A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery manufacturing, and in particular relates to a diaphragm, a battery core, a battery and a preparation method thereof. Background Art
[0002] Lithium-ion batteries are widely used in modern technology, including consumer battery products, electric vehicles, wind and solar power generation and energy storage, and household energy storage. Lithium-ion batteries can be divided into two types according to their assembly method: laminated type and wound type. Among them, wound square shell batteries have been widely used in the field of energy storage and power batteries due to their high energy density and low manufacturing cost, occupying more than 50% of the market share. However, this battery structure is prone to quality problems caused by uneven stress distribution of the core during use, which directly affects the cycle life of the battery. Therefore, how to effectively relieve stress during the battery cell cycle has become a key technical problem to improve the performance of wound square shell batteries.
[0003] In the prior art, there are two main solutions to the core stress problem. The first is the variable tension adjustment technology, that is, during the core winding process, by controlling the winding tension, it is gradually reduced as the core thickness increases, thereby reducing the winding stress of the core. This method aims to relieve internal stress by dynamically adjusting the tension, thereby extending the service life of the battery cell. The second technical solution is the positive electrode plate embossing process, in which the positive electrode plate is embossed before the core is wound to increase the thickness of the plate. In the subsequent hot pressing process, the embossing is flattened, thereby increasing the gap between the positive electrode, diaphragm and negative electrode in the core, thereby achieving the purpose of relieving the core stress. These two technical solutions have solved the core stress problem to a certain extent, but there are still many shortcomings.
[0004] Specifically, the variable tension adjustment technology mainly targets the stress source of the core during the winding process, that is, the internal stress formed by the gradual tightening of the core as the thickness of the core increases. However, in the actual use of the battery cell, the thickness change of the negative electrode during the lithiation-delithiation process and the thickness change of the positive electrode sheet will cause the internal stress of the core to gradually increase during the cycle. This is one of the important reasons for the failure of wound batteries, but the variable tension adjustment technology is powerless to this stress change and cannot effectively solve the stress problem of the battery cell during cyclic use.
[0005] On the other hand, although the embossing process of the positive electrode sheet provides a certain space for the cyclic expansion of the winding core and relieves the stress during some cycles, this process also has obvious defects. After the embossing process, the concave edges of the electrode sheet are prone to powder loss, and these dusts may pierce the diaphragm and cause the battery cell to fail. In addition, the winding core relies on the hot pressing process to convert the embossing into a flat electrode sheet, but if the flattening effect is not good, the battery cell will still have a bulge problem. During the battery cell cycle, these bulges are close to the negative electrode sheet, the local current density increases, the polarization intensifies, the side reactions are enhanced, and ultimately the performance of the battery cell is significantly reduced.
[0006] In summary, although the existing technology has achieved certain results in solving the core stress problem, it still has many defects. The variable tension adjustment technology fails to solve the problem of gradually increasing stress during the battery cell cycle, and although the positive electrode embossing process provides a certain stress relief effect, the problems of easy powder loss and poor hot pressing flattening significantly reduce the performance and service life of the battery. These technical defects show that a more effective solution is urgently needed to further improve the cycle life and overall performance of wound lithium-ion batteries. Summary of the invention
[0007] The first object of the present invention is to provide a diaphragm, a battery core, a battery and a preparation method. The diaphragm has the advantages of providing space for the cyclic expansion of the positive and negative pole pieces of the battery, thereby achieving the purpose of slowly releasing the core stress generated during the cycle.
[0008] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0009] In a first aspect, the present invention provides a separator, comprising: a base film, and soft template particles distributed on the surface of the base film and soluble in an electrolyte solution;
[0010] In an optional embodiment, the particle size of the soft template particles is 0.5 μm-5 μm;
[0011] In an optional embodiment, the surface density of the soft template particles is 0.1 g / m 2 -5 g / m 2 .
[0012] In an optional embodiment, the soft template particles have functional groups on their surfaces;
[0013] The surface of the base film is loaded with a fluorine-rich polymer;
[0014] The fluorine-rich polymer and the functional group are connected by hydrogen bond adsorption;
[0015] In an optional embodiment, the functional group includes at least one of a hydroxyl group, a carboxyl group and an aldehyde group;
[0016] In an optional embodiment, the fluorine-rich polymer includes at least one of polyvinylidene fluoride and polyvinylidene fluoride-hexafluoropropylene.
[0017] In an optional embodiment, the material of the base film includes at least one of a polypropylene membrane, a polyethylene membrane and a polyimide membrane.
[0018] In a second aspect, the present invention further provides a battery roll core, comprising a positive electrode sheet and a negative electrode sheet, and a separator as described above disposed between the positive electrode sheet and the negative electrode sheet;
[0019] The separator forms a supporting space with the positive electrode sheet and the negative electrode sheet respectively through the soft template particles on the surface of the base film.
[0020] In a third aspect, the present invention further provides a battery, comprising the battery roll core as described above, and an electrolyte solution; wherein the electrolyte solution can dissolve the soft template particles on the surface of the base film of the battery roll core after injection.
[0021] In a fourth aspect, the present invention further provides a method for preparing a diaphragm, comprising:
[0022] Dissolving a soft template raw material in a first solvent to form a homogeneous mixed solution; wherein the first solvent is a solvent capable of dissolving the soft template raw material; and the soft template raw material comprises at least one of polyvinyl pyrrolidone particles and polyethylene oxide particles;
[0023] The homogeneous mixed solution is subjected to spray drying to prepare soft template particles;
[0024] The soft template particles are dispersed in a second solvent and sprayed on the surface of the base film to obtain the diaphragm; wherein the second solvent is a solvent in which the soft template particles are not easily soluble.
[0025] In an optional embodiment, dissolving the soft template raw material in the first solvent to form a homogeneous mixed solution comprises:
[0026] Adding the soft template raw material into the first solvent, heating and stirring to obtain the homogeneous mixed solution;
[0027] In an optional embodiment, the soft template raw material includes at least one of polyvinyl pyrrolidone particles and polyethylene oxide particles;
[0028] In an optional embodiment, the mass concentration of the soft template raw material is 5wt.%-50wt.%;
[0029] In an optional embodiment, the first solvent includes at least one of water, ethanol, methanol, N,N-dimethylformamide and N-methylpyrrolidone;
[0030] In an optional embodiment, during the heating and stirring treatment, the heating temperature is 50°C-100°C;
[0031] In an optional embodiment, during the heating and stirring treatment, the stirring speed is 400 rpm-2000 rpm.
[0032] In an optional embodiment, the step of spray drying the homogeneous mixed solution to prepare soft template particles comprises:
[0033] The homogeneous mixed solution is subjected to a spray drying process by a high-pressure atomization-cyclone separation method, the homogeneous mixed solution is atomized, and blown into a cyclone separation chamber by a carrier gas to obtain the soft template particles;
[0034] In an optional embodiment, during the spray drying process, the nozzle diameter is 0.2 mm-2.0 mm;
[0035] In an optional embodiment, during the spray drying process, the pressure is 3MPa-6MPa;
[0036] In an optional embodiment, during the spray drying process, the carrier gas is nitrogen;
[0037] In an optional embodiment, during the spray drying process, the temperature of the cyclone separation chamber is 100° C.-150° C.;
[0038] In an optional embodiment, after the homogeneous mixed solution is subjected to a spray drying process using a high-pressure atomization-cyclone separation method, the homogeneous mixed solution is atomized and blown into a cyclone separation chamber by a carrier gas to obtain the soft template particles, the method further comprises:
[0039] spray drying the homogeneous mixed solution to obtain the soft template particles;
[0040] Immersing or spraying the soft template particles with a functional coupling agent to form functional groups on the surface of the soft template particles; the functional groups include at least one of hydroxyl, carboxyl and aldehyde groups;
[0041] In an optional embodiment, before dispersing the soft template particles in a second solvent and spraying the second solvent on the surface of the base film to obtain the diaphragm, the method further comprises:
[0042] A fluorine-rich polymer is sprayed on the surface of the base film to form a fluorine-rich coating on the surface of the base film; the fluorine-rich polymer includes at least one of polyvinylidene fluoride and polyvinylidene fluoride-hexafluoropropylene.
[0043] In an optional embodiment, the surface loading of the fluorine-rich polymer is 0.1 g / m 2 -1 g / m 2 .
[0044] In an optional embodiment, the soft template particles are dispersed in a second solvent and sprayed on the surface of the base film to obtain the diaphragm, comprising:
[0045] adding the soft template particles into the second solvent, stirring and mixing to obtain a mixed solution;
[0046] Spraying the mixed solution onto the surface of the base film in a high-pressure atomization manner to obtain a composite base film;
[0047] Drying the composite base film to obtain the diaphragm;
[0048] In an optional embodiment, the stirring time is 0.5 hours to 2 hours;
[0049] In an optional embodiment, the pressure of the high-pressure atomization method is 0.2MPa-1MPa;
[0050] In an optional embodiment, the nozzle diameter of the high-pressure atomization method is 2mm-5mm.
[0051] In a fifth aspect, the present invention further provides a method for preparing the battery as described above, comprising:
[0052] Prepare a battery roll core using a positive electrode sheet, a negative electrode sheet and a separator;
[0053] The battery is obtained by injecting an electrolyte solution into the battery core and dissolving the soft template particles on the surface of the base film in the battery core by using the electrolyte solution.
[0054] The present invention provides a diaphragm, comprising: a base film, and soft template particles distributed on the surface of the base film and soluble in an electrolyte solution. In the process of winding the diaphragm provided by the present invention to prepare a core, the soft template particles can increase the spatial distance between the positive electrode and the negative electrode to form an effective gap, and after the battery core is injected with an electrolyte solution, the soft template particles can dissolve in the electrolyte solution to provide space for the cyclic expansion of the positive and negative electrode plates of the battery, thereby achieving the purpose of slowly releasing the core stress generated during the cycle, and avoiding the problem of embossing the positive electrode plate used in conventional technology, resulting in poor plate flatness and easy powder loss. BRIEF DESCRIPTION OF THE DRAWINGS
[0055] Figure 1 Schematic diagram of the cross-sectional structure of the diaphragm in an embodiment of the present invention;
[0056] Figure 2 Schematic diagram of the connection form of hydrogen bonds between the fluorine-rich coating in the diaphragm and the functional groups of the soft template particles in the embodiment of the present invention;
[0057] Figure 3 Schematic diagram of the cross-sectional structure of a battery roll core in an embodiment of the present invention;
[0058] Figure 4 is a schematic diagram of a cross-sectional structure of a battery in an embodiment of the present invention;
[0059] Figure 5 Schematic diagram of the process of preparing the diaphragm in an embodiment of the present invention;
[0060] Figure 6 Schematic diagram of the process of preparing a battery in an embodiment of the present invention.
[0061] Reference numerals:
[0062] 100, battery; 11, battery core; 111, separator; 1111, base film; 11111, fluorine-rich coating; 1112, soft template particles; 11121, functional functional groups; 11122, hydrogen bonds; 112, positive electrode sheet; 113, negative electrode sheet; 114, supporting space; 12, electrolyte solution. DETAILED DESCRIPTION
[0063] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0064] refer to Figure 1 In an embodiment of the present application, a separator is provided, comprising: a base film, and soft template particles distributed on the surface of the base film and soluble in an electrolyte solution.
[0065] As mentioned above, the surface of the base film may include any one surface or both the upper and lower surfaces of the base film.
[0066] The soft template particles are distributed on the surface of the base film, and the number or density of the distribution is intended to create gaps between the positive electrode sheet and / or the negative electrode sheet and the separator in the prepared battery roll core, or to increase the spacing between the positive electrode sheet and the negative electrode sheet in the battery roll core.
[0067] The diaphragm provided in this embodiment has the soft template particles that can increase the spatial distance between the positive electrode and the negative electrode to form an effective gap during the winding process to prepare the core. After the battery core is injected with the electrolyte solution, the soft template particles can dissolve in the electrolyte solution to provide space for the expansion of the positive and negative electrode plates of the battery, thereby achieving the purpose of slowly releasing the core stress generated during the cycle, avoiding the problem of embossing the positive electrode plate used in conventional technology, resulting in poor plate flatness and easy powder loss.
[0068] Furthermore, the particle size of the soft template particles is 0.5 μm-5 μm, for example, 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, etc.
[0069] Furthermore, the surface density of the soft template particles is 0.1 g / m 2 -5 g / m 2 For example, it can be 0.1 g / m 2 , 1g / m 2 , 2g / m 2 , 3g / m 2 , 4g / m 2 , 5g / m 2 etc.
[0070] As mentioned above, if the particle size of the soft template particles is less than 0.5μm, in order to achieve the expected slow-release space, the surface density of the soft template particles needs to be increased, resulting in an overly thick soft template layer and difficulty in dissolving the electrolyte. The residual soft template particles will block the ion transmission channel, resulting in increased polarization of the battery cell, decreased capacity, and worse cycle life.
[0071] If the particles are larger than 5μm, the soft template particles are too large, resulting in a larger distance between the positive and negative electrodes. After the electrolyte dissolves the soft template particles, the fit between the separator and the positive and negative electrodes deteriorates, and wrinkles are easily generated. Wrinkles on the core will induce lithium deposition at the interface, endangering the safety and electrochemical performance of the battery cell.
[0072] As mentioned above, in the embodiments of the present application, the surface density of the soft template particles is a key parameter, which directly affects the performance of the diaphragm and the cycle life of the battery core. If the surface density is too low, it means that the soft template particles are sparsely distributed on the surface of the base film, and may not form enough support space to relieve the stress generated by the battery core during the cycle. This will lead to a decrease in battery performance and a shortened cycle life.
[0073] On the contrary, if the surface density is too high, although it can provide more support space, it may also bring some problems. First, too many soft template particles may increase the weight and volume of the separator, which will not only increase the cost of the battery, but also may affect the energy density of the battery. Secondly, if the amount of soft template particles is too much, they may not be completely dissolved during the dissolution process, and the residual particles may affect the flow of electrolytes and ion migration inside the battery, thereby affecting the performance of the battery.
[0074] Therefore, the surface density of the soft template particles is precisely limited in the embodiment of the present application, and the range is 0.1 g / m 2 -5 g / m 2 This range is set based on the optimal balance point obtained through experimental and theoretical analysis, which can ensure that the soft template particles form sufficient support space on the surface of the base film, and that the soft template particles can be completely dissolved after the electrolyte solution is injected into the battery core, thereby avoiding negative impact on battery performance.
[0075] By precisely controlling the surface density of the soft template particles, the separator in the embodiment of the present application can effectively extend the cycle life of the battery while ensuring the battery performance, thus solving some problems existing in the prior art. This method not only improves the reliability and safety of the battery, but also provides a new solution for the field of battery manufacturing technology.
[0076] For further reference, Figure 2 , the soft template particles have functional groups on their surfaces;
[0077] The surface of the base film is loaded with a fluorine-rich polymer;
[0078] The fluorine-rich polymer and the functional group are connected by hydrogen bond adsorption.
[0079] Further, the functional group includes at least one of a hydroxyl group, a carboxyl group and an aldehyde group;
[0080] Furthermore, the fluorine-rich polymer includes at least one of polyvinylidene fluoride and polyvinylidene fluoride-hexafluoropropylene.
[0081] It should be noted that after the soft template particles are set or formed on the surface of the base film, but when the battery roll and battery are installed and no electrolyte is added, the soft template particles may move to a certain extent. If the position movement occurs, some particles will agglomerate and some base film surfaces will not be covered with enough soft template particles.
[0082] If the soft template particles move to a certain extent on the surface of the base film during the installation of the battery core and the battery assembly process, the following problems may occur:
[0083] (1) Uneven electrolyte distribution: The movement of soft template particles may lead to uneven distribution of electrolyte in the separator, affecting the transmission efficiency of lithium ions and further affecting the charge and discharge performance of the battery.
[0084] (2) Increased risk of internal short circuit: The movement of soft template particles may cause uneven distance between the positive and negative electrodes, increasing the risk of internal short circuit, which may lead to decreased battery performance or even safety accidents.
[0085] (3) Increased internal resistance of the battery: If the soft template particles agglomerate or locally concentrate, the distance between the positive and negative electrodes may increase in the local area, reduce the stability of the separator, increase the internal resistance of the battery, and affect the charging and discharging efficiency of the battery.
[0086] (4) Uneven battery expansion and stress: The movement of soft template particles may cause uneven expansion and stress distribution of the battery during use, affecting the cycle stability and life of the battery.
[0087] (5) Degradation of battery performance: The curvature of the roll core has an impact on the electrical performance of lithium batteries. The unstable distribution of soft template particles may aggravate this curvature, resulting in a decrease in battery performance.
[0088] (6) Safety risks: Defects inside the battery may lead to severe self-discharge and may even cause safety problems. The movement of soft template particles may introduce such defects and increase safety risks.
[0089] In order to avoid these problems, in the embodiments of the present application, functional groups are introduced on the surface of the soft template particles, fluorine-rich polymers are loaded on the surface of the base film, and hydrogen bonds are used for adsorption connection to enhance the binding ability between the soft template particles and the base film. This design can further improve the binding strength and adsorption capacity of the soft template particles through chemical bonds when they are loaded on the surface of the base film, so that the soft template particles can be "fixed" in the relative position of the original load, reducing the movement of the soft template particles during the preparation of the battery core and the assembly of the battery, thereby improving the overall performance and reliability of the battery. Through this technical solution, the stability of the soft template particles in the battery core can be ensured, and battery performance problems caused by particle movement can be reduced.
[0090] The surface of the base film may be sprayed with a fluorine-rich polymer. The fluorine-rich polymer may be at least one of polyvinylidene fluoride and polyvinylidene fluoride-hexafluoropropylene. The sprayed fluorine-rich coating may hydrogen bond with the functional groups on the surface of the soft template particles, thereby enhancing the interaction between the soft template particles and the base film and preventing the soft template particles from falling off or powdering.
[0091] Furthermore, the material of the base film includes at least one of a polypropylene membrane, a polyethylene membrane and a polyimide membrane.
[0092] It should be noted that polypropylene (PP) separator, polyethylene (PE) separator and polyimide (PI) separator are all separator materials in lithium-ion batteries, each with its own unique properties and advantages.
[0093] Above, polypropylene (PP) separator: polypropylene is a thermoplastic polymer with excellent mechanical strength and heat resistance. PP separator is mainly used to separate the positive and negative electrodes in the battery to prevent short circuits while allowing lithium ions to move freely through the electrolyte. The main advantages of PP separators include high mechanical strength, good chemical resistance and low cost. Due to its higher melting point, PP separators can maintain good stability when the internal temperature of the battery rises, thereby improving the safety of the battery.
[0094] Above, polyethylene (PE) diaphragm: Polyethylene is a material with good flexibility and high chemical stability. PE diaphragms usually have good electrolyte wettability and can effectively improve the ionic conductivity of the battery. In addition, PE diaphragms have a low melting point and can melt when abnormal temperature rises inside the battery, thereby closing the pores between the electrodes and automatically shutting down the battery, further improving the safety performance of the battery. This characteristic enables the PE diaphragm to play a self-protection function when the battery overheats.
[0095] Above, polyimide (PI) separator: Polyimide is a high-performance engineering plastic with excellent high temperature resistance and mechanical strength. PI separators exhibit excellent heat resistance and chemical corrosion resistance in battery applications, and can maintain stable performance under high temperature and harsh environments. PI separators also have high electrical insulation and good dimensional stability, which can effectively prevent the occurrence of internal short circuits and other faults in the battery. Due to its excellent comprehensive performance, PI separators are often used in high-performance and high-safety lithium-ion batteries.
[0096] Furthermore, the soft template particles are prepared from soft template raw materials;
[0097] The soft template raw material includes at least one of polyvinyl pyrrolidone particles and polyethylene oxide particles. Polyvinyl pyrrolidone and polyethylene oxide have good compatibility with ester-based electrolytes (ethylene carbonate, cyclic carbonate, etc.) widely used in the current lithium battery industry, which can ensure that the soft template particles can be fully dissolved in the electrolyte to achieve the technical goal of releasing the slow-release space.
[0098] In addition, reference Figure 3 , the present application also provides a battery roll core in an embodiment, comprising a positive electrode sheet and a negative electrode sheet, and a separator as described above disposed between the positive electrode sheet and the negative electrode sheet;
[0099] The separator forms a supporting space with the positive electrode sheet and the negative electrode sheet respectively through the soft template particles on the surface of the base film.
[0100] In addition, reference Figure 4 In an embodiment of the present application, a battery is also provided, comprising a battery core as described above, and an electrolyte solution; wherein the electrolyte solution can dissolve the soft template particles on the surface of the base film of the battery core after injection.
[0101] In addition, reference Figure 5 In an embodiment of the present application, a method for preparing the above-mentioned diaphragm is also provided, comprising:
[0102] Step S1, dissolving a soft template raw material in a first solvent to form a homogeneous mixed solution; wherein the first solvent is a solvent capable of dissolving the soft template raw material; the soft template raw material comprises at least one of polyvinyl pyrrolidone particles and polyethylene oxide particles;
[0103] Step S2, spray drying the homogeneous mixed solution and performing oxygen plasma treatment to prepare soft template particles;
[0104] Step S3, dispersing the soft template particles in a second solvent, and spraying the second solvent on the surface of the base film to obtain the diaphragm; wherein the second solvent is diethyl ether or dipropyl ether solvent.
[0105] Furthermore, dissolving the soft template raw material in the first solvent to form a homogeneous mixed solution includes:
[0106] Adding the soft template raw material into the first solvent, heating and stirring to obtain the homogeneous mixed solution;
[0107] Furthermore, the soft template raw material includes at least one of polyvinyl pyrrolidone particles and polyethylene oxide particles;
[0108] Furthermore, the mass concentration of the soft template raw material is 5wt.%-50wt.%; for example, it can be 5wt.%, 10wt.%, 20wt.%, 30wt.%, 40wt.%, 50wt.%, etc.
[0109] Further, the first solvent includes at least one of water, ethanol, methanol, N,N-dimethylformamide and N-methylpyrrolidone;
[0110] As mentioned above, water may include but is not limited to deionized water, ultrapure water, distilled water, etc.; ethanol may include but is not limited to alcohol, anhydrous ethanol, analytical grade ethanol; methanol may include but is not limited to anhydrous methanol, analytical grade ethanol.
[0111] Furthermore, during the heating and stirring treatment, the heating temperature is 50°C-100°C; for example, it can be 50°C, 60°C, 80°C, 100°C, etc.
[0112] Furthermore, during the heating and stirring treatment, the stirring speed is 400 rpm-2000 rpm. For example, it can be 400 rpm, 500 rpm, 1000 rpm, 1500 rpm, 2000 rpm, etc.
[0113] Furthermore, the homogeneous mixed solution is spray-dried to prepare soft template particles, comprising:
[0114] The homogeneous mixed solution is subjected to a spray drying process by a high-pressure atomization-cyclone separation method, the homogeneous mixed solution is atomized, and blown into a cyclone separation chamber by a carrier gas to obtain the soft template particles;
[0115] Furthermore, during the spray drying process, the nozzle diameter is 0.2 mm-2.0 mm; for example, it can be 0.2 mm, 1.0 mm, 1.5 mm, 2.0 mm, etc.
[0116] Furthermore, during the spray drying process, the pressure is 3MPa-6MPa; for example, it can be 3MPa, 4MPa, 5MPa, 6MPa, etc.
[0117] Furthermore, during the spray drying process, the carrier gas is nitrogen;
[0118] Furthermore, during the spray drying process, the temperature of the cyclone separation chamber is 100° C.-150° C. For example, it can be 100° C., 120° C., 140° C., 150° C., etc.
[0119] Furthermore, after the homogeneous mixed solution is subjected to a spray drying process by a high-pressure atomization-cyclone separation method, the homogeneous mixed solution is atomized and blown into a cyclone separation chamber by a carrier gas to obtain the soft template particles, the method further comprises:
[0120] spray drying the homogeneous mixed solution to obtain the soft template particles;
[0121] Immersing or spraying the soft template particles with a functional coupling agent to form functional groups on the surface of the soft template particles; the functional groups include at least one of hydroxyl, carboxyl and aldehyde groups;
[0122] Furthermore, before dispersing the soft template particles in a second solvent and spraying them on the surface of the base film to obtain the diaphragm, the process further includes:
[0123] A fluorine-rich polymer is sprayed on the surface of the base film to form a fluorine-rich coating on the surface of the base film; the fluorine-rich polymer includes at least one of polyvinylidene fluoride and polyvinylidene fluoride-hexafluoropropylene.
[0124] Furthermore, the surface loading of the fluorine-rich polymer is 0.1 g / m 2 -1 g / m 2 For example, it can be 0.1 g / m 2 , 0.5g / m 2 , 0.7g / m 2 , 1.0g / m 2 etc.
[0125] Furthermore, the soft template particles are dispersed in a second solvent and sprayed on the surface of the base film to obtain the diaphragm, comprising:
[0126] adding the soft template particles into the second solvent, stirring and mixing to obtain a mixed solution;
[0127] Spraying the mixed solution onto the surface of the base film in a high-pressure atomization manner to obtain a composite base film;
[0128] Drying the composite base film to obtain the diaphragm;
[0129] Furthermore, the stirring time is 0.5 hours to 2 hours; for example, it can be 0.5 hours, 1 hour, 1.5 hours, 2 hours, etc.
[0130] Furthermore, the pressure of the high-pressure atomization method is 0.2MPa-1MPa; for example, it can be 0.2MPa, 0.5MPa, 1MPa / hour, etc.
[0131] Furthermore, the nozzle diameter of the high-pressure atomization method is 2 mm-5 mm, for example, 2 mm, 3 mm, 4 mm, 5 mm, etc.
[0132] In addition, reference Figure 5 In an embodiment of the present application, a method for preparing the battery as described above is also provided, comprising:
[0133] Step S100, preparing a battery roll core using a positive electrode sheet, a negative electrode sheet and a separator;
[0134] Step S200, injecting an electrolyte solution into the battery core, and using the electrolyte solution to dissolve the soft template particles on the surface of the base film of the battery core, so as to obtain the battery.
[0135] The present invention is further described below by means of specific examples, but it should be understood that these examples are only used for more detailed description and should not be construed as limiting the present invention in any form.
[0136] Table 1. Main ingredients and raw materials in Examples and Comparative Examples
[0137] In the above table, "Shi" at the header corresponds to the abbreviation of "Example", e.g., "Shi 1" means "Example 1"; "Dui" corresponds to the abbreviation of "Comparative Example", and "Dui 1" means "Comparative Example 1", and so on.
[0138] Table 2. Table of Main Parameters in Examples and Comparative Examples
[0139] item Real 1 Real 2 Real 2 Reality 3 1 2 3 Heating and stirring temperature ℃ 50 50 75 100 50 50 50 Stirring speed rpm 400 400 1000 2000 400 400 400 Nozzle diameter mm 0.2 0.2 1.0 2.0 3.0 0.2 0.2 Pressure MPa 3 3 5 6 3 3 3 Cyclone separation chamber temperature 100 100 125 150 100 100 100 Stirring time 0.5 0.5 1 2 0.5 0.5 0.5 High pressure atomization mode pressure MPa 0.2 0.2 0.5 1 0.2 0.2 0.2 High pressure atomization nozzle diameter mm 2 2 3 5 2 2 2
[0140] Example 1:
[0141] In this example, a stress-releasable core and a core for a roll are prepared, and the specific parameters and components can be referred to in Table 1 and Table 2.
[0142] Experimental method:
[0143] (1) Preparation of soft template particles:
[0144] The soft template raw material, polyvinylpyrrolidone particles, are heated and dissolved in water, and the solution concentration is 5 wt.%.
[0145] During the heating and stirring treatment, the heating temperature is 50 °C; the stirring speed is 400 rpm.
[0146] The homogeneous mixed solution is subjected to spray drying treatment. During the spray drying treatment, the nozzle diameter is 0.2 mm; the pressure is 3 MPa; the carrier gas is nitrogen; the temperature of the cyclone separation chamber is 100 °C - 150 °C.
[0147] The above materials are subjected to oxygen plasma treatment to prepare soft template particles;
[0148] (2) Preparation of the base film:
[0149] Select the corresponding base film according to the materials in Table 1.
[0150] (3) Spraying of soft template particles:
[0151] The soft template particles are dispersed in an ether solvent and sprayed on the surface of the base film, and the diaphragm is obtained after drying treatment. Further, the stirring time is 0.5 hours; the pressure of the high-pressure atomization method is 0.2 MPa; the nozzle diameter of the high-pressure atomization method is 2 mm.
[0152] (4) Preparation of the core:
[0153] The battery core is prepared using the composite diaphragm prepared above; an electrolyte solution is injected into the battery core, and the soft template particles on the surface of the base film of the battery core are dissolved by the electrolyte solution to obtain the battery.
[0154] Embodiment 2:
[0155] In this embodiment, a stress-releasing core diaphragm and a core are prepared. The specific parameters and components thereof can be referred to Table 1 and Table 2.
[0156] Experimental methods:
[0157] (1) Preparation of soft template particles
[0158] Polyvinyl pyrrolidone particles, a raw material of the soft template, are heated and dissolved in water, and the concentration of the solution is 5 wt.%.
[0159] During the heating and stirring treatment, the heating temperature is 50° C. and the stirring speed is 400 rpm.
[0160] The homogeneous mixed solution is subjected to spray drying treatment. During the spray drying treatment, the nozzle diameter is 0.2 mm; the pressure is 3 MPa; the carrier gas is nitrogen; and the temperature of the cyclone separation chamber is 100° C.-150° C.
[0161] The above materials are subjected to oxygen plasma treatment to prepare soft template particles;
[0162] The soft template particles are sprayed with a functional coupling agent to form hydroxyl functional groups on the surface of the soft template particles.
[0163] (2) Preparation of base film of fluorine-rich coating:
[0164] The surface of the polypropylene base film is sprayed with a fluorine-rich polymer to form a fluorine-rich coating.
[0165] The surface loading of the fluorine-rich polymer is 0.1 g / m 2 .
[0166] (3) Spraying soft template particles:
[0167] The soft template particles are dispersed in ether solvent and sprayed on the surface of the base film, and the diaphragm is obtained after drying. Furthermore, the stirring time is 0.5 hours; the pressure of the high-pressure atomization method is 0.2 MPa; the nozzle diameter of the high-pressure atomization method is 2 mm.
[0168] (4) Preparation of core:
[0169] A battery core is prepared using the composite separator prepared as described above; an electrolyte solution is injected into the battery core, and the soft template particles on the surface of the base film of the battery core are dissolved by the electrolyte solution to obtain the battery.
[0170] Embodiment 3:
[0171] In this example, a diaphragm and a core that can relieve core stress were prepared.
[0172] Experimental methods:
[0173] The method is basically the same as in Example 2, with specific reference to Table 1 and Table 2.
[0174] Embodiment 3:
[0175] In this example, a diaphragm and a core that can relieve core stress were prepared.
[0176] Experimental methods:
[0177] The method is basically the same as in Example 2, with specific reference to Table 1 and Table 2.
[0178] Comparative Example 1:
[0179] In this comparative example, a diaphragm and a core that can relieve the stress of the core were prepared.
[0180] Experimental methods:
[0181] The method is basically the same as in Example 1. In the process of preparing the base film, no fluorine-rich coating is performed. Polyethylene without fluorinated functional groups is coated. The adsorption effect of the base film on the soft template particles is greatly reduced. For details, refer to Table 1 and Table 2.
[0182] Comparative Example 2: A diaphragm and a core that can relieve core stress were prepared.
[0183] Experimental methods:
[0184] The method is basically the same as that in Example 1. In the process of preparing the soft template particles, the nozzle diameter is increased, the particle size of the soft template particles is increased, the distance between the positive and negative electrodes in the winding core is increased, and the polarization of the battery cell is aggravated. For details, refer to Table 1 and Table 2.
[0185] Comparative Example 3: A diaphragm and a core that can relieve core stress were prepared.
[0186] Experimental methods:
[0187] The method is basically the same as that in Example 1. In the process of loading the soft template particles, the loading amount of the soft template particles is increased. After assembling into a battery cell, the electrolyte cannot completely eliminate the soft template particles, resulting in the obstruction of ion diffusion in the battery, aggravated polarization, and decreased battery cell performance. For details, refer to Table 1 and Table 2.
[0188] Comparative test experiment:
[0189] 1. Experimental methods:
[0190] (1) Test experiment 1: Test the capacity retention rate of the battery cell after 500 cycles.
[0191] The greater the capacity retention rate, the better the cycle stability of the battery cell. This highlights the important role of the stress-relieving separator in the core winding.
[0192] (2) Test experiment 2: After the core is cycled for 500 times, the expansion force of the square aluminum shell is tested. The greater the expansion force, the greater the stress of the core and the worse the stress relief effect.
[0193] (3) Test experiment 3: Test the energy efficiency of the battery cell. The lower the energy efficiency of the battery cell, the greater the voltage difference between the positive and negative electrodes in the battery cell, and the more serious the polarization, which means that the soft template particles are not completely dissolved by the electrolyte. The residual soft template particles will hinder ion transmission.
[0194] 2. Experimental results:
[0195] item Real 1 Real 2 Real 2 Reality 3 1 2 3 Capacity retention rate (%) 94.3 95.2 94.9 90.6 91.6 90.3 Expansion force(kN) 9.5 8.1 7.7 10.2 7.3 10.5 Energy efficiency (%) 94.2 94.0 94.2 94.3 92.8 89.5
[0196] analyze:
[0197] Comparative Example 1 uses polyethylene without fluorinated functional groups as the coating of the base film. Its interaction with the soft template particles is weak, and the soft template particles are easily detached from the surface of the base film, resulting in a weakened ability to release the stress of the winding core. Compared with Example 1, the expansion force of the winding core increased by 0.7 kN, and the cycle capacity retention rate decreased by 3.7%.
[0198] Comparative Example 2 uses soft template particles with a larger particle size. The larger the soft template particle size, the larger the expansion stress release space provided, but it will also increase the physical distance between the positive and negative electrodes, increase the ion diffusion distance, and increase the polarization of the battery cell. Compared with Example 1, the energy efficiency of the battery cell in Comparative Example 2 decreased by 1.4%, and the capacity retention rate decreased by 2.7%.
[0199] The surface density of the soft template particles in Comparative Example 3 is greater. The higher the surface density of the soft template particles, the more difficult it is for the electrolyte to dissolve the soft template particles. The remaining soft template particles will (1) increase the distance of ion diffusion and increase the polarization of the battery cell; (2) fail to release space, resulting in a weakened effect on the stress release of the winding core. Compared with Example 1, the winding core stress of Comparative Example 3 increased by 1kN, and the energy efficiency of the battery cell decreased by 4.7%.
[0200] The above are preferred implementation modes and corresponding embodiments of the present invention. It should be pointed out that, for those skilled in the art, without departing from the creative concept of the present invention, several modifications and improvements may be made, including but not limited to the adjustment of proportions, processes, dosages and reaction vessels, which all fall within the scope of protection of the present invention.
Claims
1. A diaphragm, It is characterized in that include: A base film, and soft template particles distributed on the surface of the base film and soluble in an electrolyte solution; Preferably, the particle size of the soft template particles is 0.5 μm-5 μm; Preferably, the surface density of the soft template particles is 0.1 g / m 2 -5 g / m 2 .
2. The diaphragm according to claim 1, It is characterized in that The soft template particles have functional groups on their surfaces; The surface of the base film is loaded with a fluorine-rich polymer; The fluorine-rich polymer and the functional group are connected by hydrogen bond adsorption; Preferably, the functional group includes at least one of a hydroxyl group, a carboxyl group and an aldehyde group; Preferably, the fluorine-rich polymer includes at least one of polyvinylidene fluoride and polyvinylidene fluoride-hexafluoropropylene.
3. The diaphragm according to claim 1, It is characterized in that The material of the base film includes at least one of a polypropylene membrane, a polyethylene membrane and a polyimide membrane.
4. A battery roll core, It is characterized in that A method comprising: comprising a positive electrode sheet and a negative electrode sheet, and a separator according to any one of claims 1 to 3 disposed between the positive electrode sheet and the negative electrode sheet; The separator forms a supporting space with the positive electrode sheet and the negative electrode sheet respectively through the soft template particles on the surface of the base film.
5. A battery, It is characterized in that It comprises the battery roll core as claimed in claim 4, and an electrolyte solution; wherein the electrolyte solution can dissolve the soft template particles on the surface of the base film of the battery roll core after being injected.
6. A method for preparing the diaphragm according to any one of claims 1 to 3, It is characterized in that include: Dissolving a soft template raw material in a first solvent to form a homogeneous mixed solution; wherein the first solvent is a solvent capable of dissolving the soft template raw material; and the soft template raw material comprises at least one of polyvinyl pyrrolidone particles and polyethylene oxide particles; The homogeneous mixed solution is spray-dried to prepare soft template particles; The soft template particles are dispersed in a second solvent and sprayed on the surface of the base film to obtain the diaphragm; wherein the second solvent is a solvent in which the soft template particles are not easily soluble.
7. The method for preparing the diaphragm according to claim 6, It is characterized in that The step of dissolving the soft template raw material in the first solvent to form a homogeneous mixed solution comprises: Adding the soft template raw material into the first solvent, heating and stirring to obtain the homogeneous mixed solution; Preferably, the soft template raw material includes at least one of polyvinyl pyrrolidone particles and polyethylene oxide particles; Preferably, the mass concentration of the soft template raw material is 5wt.%-50wt.%; Preferably, the first solvent comprises at least one of water, ethanol, methanol, N,N-dimethylformamide and N-methylpyrrolidone; Preferably, during the heating and stirring treatment, the heating temperature is 50°C-100°C; Preferably, during the heating and stirring treatment, the stirring speed is 400 rpm-2000 rpm.
8. The method for preparing the diaphragm according to claim 6, It is characterized in that The step of spray drying the homogeneous mixed solution to prepare soft template particles comprises: The homogeneous mixed solution is subjected to a spray drying process by a high-pressure atomization-cyclone separation method, the homogeneous mixed solution is atomized, and blown into a cyclone separation chamber by a carrier gas to obtain the soft template particles; Preferably, during the spray drying process, the nozzle diameter is 0.2 mm-2.0 mm; Preferably, during the spray drying process, the pressure is 3MPa-6MPa; Preferably, during the spray drying process, the carrier gas is nitrogen; Preferably, during the spray drying process, the temperature of the cyclone separation chamber is 100° C.-150° C.; Preferably, the method further comprises: spray drying the homogeneous mixed solution by a high-pressure atomization-cyclone separation method, atomizing the homogeneous mixed solution, blowing the homogeneous mixed solution into a cyclone separation chamber by a carrier gas, and obtaining the soft template particles. spray drying the homogeneous mixed solution to obtain the soft template particles; Immersing or spraying the soft template particles with a functional coupling agent to form functional groups on the surface of the soft template particles; the functional groups include at least one of hydroxyl, carboxyl and aldehyde groups; Preferably, before dispersing the soft template particles in a second solvent and spraying the particles on the surface of the base film to obtain the diaphragm, the method further comprises: Spraying a fluorine-rich polymer on the surface of the base film to form a fluorine-rich coating on the surface of the base film; the fluorine-rich polymer includes at least one of polyvinylidene fluoride and polyvinylidene fluoride-hexafluoropropylene; Preferably, the surface loading of the fluorine-rich polymer is 0.1 g / m 2 -1 g / m 2 .
9. The method for preparing the diaphragm according to claim 6, It is characterized in that The method of dispersing the soft template particles in a second solvent and spraying the second solvent on the surface of the base film to obtain the diaphragm comprises: adding the soft template particles into the second solvent, stirring and mixing to obtain a mixed solution; Spraying the mixed solution onto the surface of the base film in a high-pressure atomization manner to obtain a composite base film; Drying the composite base film to obtain the diaphragm; Preferably, the stirring time is 0.5 hours to 2 hours; Preferably, the pressure of the high-pressure atomization method is 0.2MPa-1MPa; Preferably, the nozzle diameter of the high-pressure atomization method is 2mm-5mm.
10. A method for preparing a battery as claimed in claim 5, It is characterized in that include: Prepare a battery roll core using a positive electrode sheet, a negative electrode sheet and a separator; The battery is obtained by injecting an electrolyte solution into the battery core and dissolving the soft template particles on the surface of the base film in the battery core by using the electrolyte solution.
